Prevalence and Risk Factors of Anemia in Chronic Kidney Disease Patients with Diabetes: A Cross-Sectional Study (Medical Forum Monthly, 2024)
Objective: To assess the prevalence of anemia inpatients of chronic kidney disease patients secondary to diabetes.Study Design: A Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the Department of Nephrology and Hemodialysis, Central Park Teaching Hospital, Lahore from December 2022 to May 2023.Methods: Non-random convenient sampling technique was employed and patients with age of 18 to 64 who are diagnosed cases of CKD stage 3 or above with GFR < 60 ml/min/1.73 m2 were recruited in the study. Post stratification chi-square test was applied and p-values < 0.05 was considered statistically significant.Results: A total of 323 patients were recruited with the mean age of 42.76 + 11.54 years with age range of 21 to 60 years. Anemia was assessed in all the study participants; it showed the prevalence of anemia in chronic kidney diseased patients secondary to diabetes was noted as 31.3% showing that 101 patients out of 312 had anemia. Females are more prone to develop anemia in diabetic chronic kidney diseased patients when compared to males with p value of 0.039.Conclusion: Customized therapy and individualized interventions can be designed that are in tune with the causes of anemia in this category of patient thus enhancing clinical outcomes.